2013
DOI: 10.3109/14767058.2013.807235
|View full text |Cite
|
Sign up to set email alerts
|

Uterine prolapse in pregnancy: risk factors, complications and management

Abstract: Presentation of uterine prolapse is a rare event in a pregnant woman, which can be pre-existent or else manifest in the course of pregnancy. Complications resulting from prolapse of the uterus in pregnancy vary from minor cervical infection to spontaneous abortion, and include preterm labor and maternal and fetal mortality as well as acute urinary retention and urinary tract infection. Moreover, affected women may be at particular risk of dystocia during labor that could necessitate emergency intervention for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 55 publications
1
66
0
6
Order By: Relevance
“…Having more than one vaginal birth and the use of forceps or vacuum during prolonged labour are the important risk factors for prolapse. Other predisposing factors include obesity, connective tissue disease, chronic coughing, ethnic origin and family history (3,4). In our case, the prolapse occurred soon after delivery of her first baby and persisted during the subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 62%
“…Having more than one vaginal birth and the use of forceps or vacuum during prolonged labour are the important risk factors for prolapse. Other predisposing factors include obesity, connective tissue disease, chronic coughing, ethnic origin and family history (3,4). In our case, the prolapse occurred soon after delivery of her first baby and persisted during the subsequent pregnancies.…”
Section: Discussionmentioning
confidence: 62%
“…There is no valid evidence about the benefits of systemic antibiotic treatment. Pessary treatment is often required only until the fifth month of pregnancy when the uterus usually lifts out of the pelvis, and, as a result, the symptoms related with uterine prolapse are alleviated [2,8]. Abnormalities of labor are observed more frequently in women with pregnancy-associated uterine prolapse.…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
“…Moreover, uterine prolapse may cause cervical infection and bleeding which eventually lead to the scarring and fibrosis of cervical tissue. These alterations may result in secondary arrest of the cervical dilatation [8,9]. It has been previously reported that spontaneous vaginal delivery is successfully achieved in 40% to 80% of the women with pregnancy-related uterine prolapse, but instrumental deliveries and deliveries by cesarean section occur with some frequency.…”
Section: Journal Of Clinical and Analytical Medicinementioning
confidence: 99%
See 2 more Smart Citations